Diseño de una cámara climatizada, automatizada, con manejo de información por telemetría y condiciones operativas controladas para pruebas de equipos y materiales (2018)
This research and design work has been developed based on the current need to have a test room for the evaluation and certification of equipment regulated by the Technical Regulation of Labeling - RETIQ that requires a heated chamber to assess the energy efficiency of the domestic and commercial refrigeration appliances, according to operating parameters established in the current national regulations. The variables of the environment that are required to control inside the heated chamber were characterized originally according to the general conditions of the tests for the equipment to be evaluated, establishing the operating ranges for the temperature (2 ° C - 45 ° C), relative humidity (50% - 98%) and air velocity (0.254 m / s) in the test laboratories. The thermal load of cooling and heating was calculated for each of the test laboratories and the air conditioning systems were selected in accordance with the established operating parameters; In the same way, the instrumentation and the elements for the control of the air conditioning equipment used in the chamber were selected. Finally, the costs of the implementation of the project were determined in accordance with the materials, equipment and control systems selected for its operation.